New records of jumping spiders (Araneae: Salticidae) for Slovenia - Rok Kostanjšek; Cene Fišer (Natura Sloveniae)
Eight species of jumping spiders, new for Slovenian fauna have been recorded: Aelurillus v-insignitus (Clerck, 1758), Icius subinermis Simon, 1937, Phlegra bresnieri (Lucas, 1846), Phlegra cinereofasciata (Simon, 1868), Pseudeuophrys vafra (Blackwall, 1867), Salticus unciger (Simon, 1868), Sitticus inexpectus Logunov & Kronstedt, 1997, Sitticus terebratus (Clerk, 1757).